Functions of Construction of Laws and Regulations for Art Education in Chinese Schools - Tao, Tingting; Amponstira, Fuangfa (วารสารบัณฑิตศาส์น มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2023)
The development of art education in school depends on the formulation and implementation of laws and regulations for art education in school, which is the basic guarantee of art education in school. This research takes the construction of laws and regulations for art education in Chinese schools since 1979 as the research object, explore its function according to the change of different political structure. Through a large number of analysis of literature, the researcher hopes that through this study can make certain contributions to the good development of art education in school. Through this research, the achievements and shortcomings of the construction of laws and regulations for school art education are summarized; Reveal the essence and positive role of the construction of laws and regulations for art education in school; Understanding the construction of laws and regulations for art education in school is the legal guarantee for the healthy development of art education. The research of the above problems is to obtain first-hand information from field investigation and obtain data through qualitative and quantitative research and analysis methods. The purpose is to further deepen the construction of laws and regulations for school art education and demonstrate the theoretical and practical functions of the construction of laws and regulations for art education. This paper is divided into five chapters.